Konseling pola makan gizi seimbang pada atlet remaja di Pertukaran Pemuda antar Provinsi (PPAP) dan Sentra Pembinaan Olahragawan Berbakat Nasional (SPOBNAS) Wisma Atlet Jakabaring Palembang - Fatmalina Febry; Ditia Fitri Arinda; Ira Dewi Ramadhani Ramadhani; Naila Syafira (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Balanced Nutrition Counseling on Dietary Patterns among Adolescent Athletes at Pertukaran Pemuda antar Provinsi (PPAP) dan Sentra Pembinaan Olahragawan Berbakat Nasional (SPOBNAS), Jakabaring Athlete Dormitory, Palembang. Adolescent athletes have high energy and nutrient requirements because they are in a period of growth while also engaging in moderate- to high-intensity physical training. However, irregular eating patterns and low nutrition knowledge remain common problems among athletes living in training dormitories. This activity aimed to assess nutrient adequacy levels and provide balanced nutrition counseling for adolescent athletes at the Jakabaring Athlete Dormitory, Palembang. The methods included anthropometric measurements, dietary intake assessment using a 24-hour food recall, analysis of nutrient adequacy levels, and nutrition counseling. The subjects consisted of 21 adolescent athletes from various sports disciplines. The results showed that most athletes experienced severe deficits in energy intake (81%), protein (81%), fat (33.3%), and carbohydrates (90.5%). These conditions were influenced by habits of skipping meals, low consumption of snacks, and limited awareness of the importance of balanced nutrition. Nutrition counseling emphasized the implementation of balanced dietary patterns, meal timing management, utilization of available foods in the dormitory, selection of healthier snacks, and appropriate fluid intake management. This activity demonstrates that sports nutrition counseling plays an important role in improving athletes’ knowledge and awareness of meeting nutritional requirements, thereby supporting the health, fitness, and performance of adolescent athletes.